2015
DOI: 10.1039/c5ob01739d
|View full text |Cite
|
Sign up to set email alerts
|

The development of a short route to the API ropinirole hydrochloride

Abstract: A four-step, three-stage synthesis of the API ropinirole hydrochloride has been developed from a commercially available naphthalene derivative. The new route has half the step-count and twice the overall yield of the current manufacturing process. Key features of the synthesis are a regioselective Birch reduction and an ozonolysis with concomitant ring closure to induce the required ring contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Tarur Harrowven et al reported two ways of ropinirole synthesis involving the reductive alkylation of bis-n-propylamine. 162 A reaction of n-Pr 2 NH with aldehyde 2.29.b in the presence of 2.3 equiv of sodium cyanoborohydride quantitatively furnished amine 2.29.c (6.7 g, 49% RME), which can be converted to ropinirole (Scheme 79).…”
Section: Galanthaminementioning
confidence: 99%
“…Tarur Harrowven et al reported two ways of ropinirole synthesis involving the reductive alkylation of bis-n-propylamine. 162 A reaction of n-Pr 2 NH with aldehyde 2.29.b in the presence of 2.3 equiv of sodium cyanoborohydride quantitatively furnished amine 2.29.c (6.7 g, 49% RME), which can be converted to ropinirole (Scheme 79).…”
Section: Galanthaminementioning
confidence: 99%
“…We investigated the viability of the methodology on other naphthalene derivatives, in particular 1-aminonapthalene 1b which is of interest because of its use in the synthesis of the API Ropinirole·HCl, developed by Harrowven and co-workers ( Figure 5 a). 56 The reduction product 2b was formed with high yield and selectivity, with only a trace of the over-reduction product, 5-aminotetralin, present. A sample (100 mL) was collected once the reactor was at the steady state, which was worked up to give an isolated yield of 95% for 2b which equates to a projected productivity for 2b of 114 g day –1 (782 mmol day –1 ).…”
Section: Resultsmentioning
confidence: 97%
“…13 1-Amino-5,8-dihydronapthalene 2b. 57 Isolated as a reddish solid. 1 The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.oprd.2c00108.…”
mentioning
confidence: 99%
“…We envisaged that water might act as a nucleophile to promote this transformation. Therefore, we conducted the reaction in t BuOH/H 2 O = 9:1, which gave 5a and 5b in 93 % and 58 % yield respectively. Interestingly, substrate bearing amide group, such as 3‐(5‐bromo‐1 H ‐indol‐3‐yl)propanamide 4c also led to 5a in 57 % yield, which revealed that the reaction proceeded via nucleophilic attack of oxygen on amide and followed by hydrolysis of imine intermediate (Scheme ).…”
Section: Resultsmentioning
confidence: 99%